Introduction to TCP/IP internetworking - Bush, Patrick J. (South-Western Educational, 2000)
TCP/IP at a glance. TCP/IP test utilities and name resolution. Digging deeper into Microsoft TCP/IP. IP addressing and TCP/IP subnetting demystified. IP routing. NetBIOS, browsing, and WINS. The domain name system and Microsoft DNS server...